Packaging perspective of milk and dairy products - Ščetar, Mario (Array, 2019)
Packaging of dairy products develops continuously along with advances in material technologies, which are in turn a response to demands of consumers. This article aimed to give an overview of currently available dairy packaging systems. Novel dairy packaging systems include new packaging technologies such as the modified atmosphere packaging (MAP) that is widely used nowadays, especially for dairy product like cheese. Application of edible packaging could significantly reduce the costs of cheese packaging by reducing the amount of usually required packaging material. Nanomaterials and active packaging might be useful for extending the shelf life of dairy products by reducing material permeability or negative sensory characteristics of batch processing. Forms of active packaging relevant to dairy foods include oxygen scavenging, carbon dioxide absorbers, moisture and/or flavour/odour taints absorbers; releasing compounds (carbon dioxide, ethanol, antioxidants and/or other preservatives); maintaining temperature control and/or compensating temperature changes and antimicrobial packaging. Antimicrobial packaging is gaining interest from packaging scientists and industry due to its potential for providing quality and their safety benefits. The greatest challenge from the ecological point of view is biodegradable packaging. The main challenges for low waste materials are the durability of the packaging correlated with product shelf life as well as the ecological perspective.